The ballistics of seventeenth century musket balls. Issue 1 (2nd January 2019) - Miller, David P.; Allsop, Derek; Carr, Debra J.
ABSTRACT: This paper investigates the firing of seventeenth Century musket balls. Prior to this research, the main concerns with making range predictions were associated with the deformed shape of the musket balls affecting their drag coefficient and therefore their distance to ground impact. However, the distance due to bounce and roll after initial impact has been unknown. In this work, the distance travelled after the first ground impact greatly exceeded expectations, with the musket balls approximately doubling the distance to their final resting positions. From these findings the initial factors thought to have had high relevance to the final resting position of the musket ball (velocity variation and drag co-efficient) become less significant and factors such as ground hardness become more prominent. The knowledge gained during this investigation will allow more accurate information to be obtained on the firing positions of opposing forces during conflicts in the English Civil War.